The HASHTAG project I: A survey of CO(3–2) emission from the star forming disc of M31 - Li, Z; Li, Z; Smith, MWL; Wilson, CD; Gao, Y; Eales, SA; Ao, Y; Bureau, M; Chung, A; Davis, TA; De Grijs, R; Eden, DJ; et al. (Oxford University Press, 2019)
We present a CO(3–2) survey of selected regions in the M31 disc as part of the JCMT large programme, HARP and SCUBA-2 High-Resolution Terahertz Andromeda Galaxy Survey (HASHTAG). The 12 CO(3–2) fields in this survey cover a total area of 60 arcmin2, spanning a deprojected radial range of 2–14 kpc across the M31 disc. Combining these observations with existing IRAM 30 m CO(1–0) observations and JCMT CO(3–2) maps of the nuclear region of M31, as well as dust temperature and star formation rate surface density maps, we are able to explore the radial distribution of the CO(3–2)/CO(1–0) integrated intensity ratio (R31) and its relationship with dust temperature and star formation. We find that the value of R31 between 2 and 9 kpc galactocentric radius is 0.14, significantly lower than what is seen in the nuclear ring at 1 kpc (R31 ∼ 0.8), only to rise again to 0.27 for the fields centred on the 10 kpc star forming ring. We also found that R31 is positively correlated with dust temperature, with Spearman’s rank correlation coefficient ρ = 0.55. The correlation between star formation rate surface density and CO(3–2) intensity is much stronger than with CO(1–0), with ρ = 0.54 compared to –0.05, suggesting that the CO(3–2) line traces warmer and denser star forming gas better. We also find that R31 correlates well with star formation rate surface density, with ρ = 0.69.